Disparitas, Konvergensi, dan Determinan Produktivitas Tenaga Kerja Regional di Indonesia - Yuniasih, Aisyah Fitri; Firdaus, Muhammad; Fahmi, Idqan (UI Scholars Hub, 2013)
Indonesia has been still experiencing regional economic disparity problems, including in labour productivity. This study employs dynamic panel approach to analyze convergence and to identify determinants of regional labour productivity during the period of 1987-2011. The System Generalized Method of Moments (Sys-GMM) estimation results show that regional convergence process occurs with speed of convergence of 0.06518 per year. Physical capital stock, human capital stock, total trade, and real wage give positive impacts. Therefore, government should prioritize in overcoming labour productivity disparity in Eastern Indonesia in which are more unequal than in Western Indonesia where interventions should be greater for provinces with lower labour productivity.